Pengembangan Video Animasi untuk Meningkatkan Hots pada Siswa Kelas V di SDS Amir Hamzah - Dalimunthe, Siti Rubiah; Simatupang, Wilna Wulan Suci; Nasution, Mona Hijriah; Siagian, Eka Anggraini (JURNAL PEMBELAJARAN DAN MATEMATIKA SIGMA (JPMS), 2018)
This study aims to develop effective animated video learning media in Natural Sciences subjects. Material on Natural Resources (SDA) to improve higher-order thinking skills and learning outcomes, at SDS Amir Hamzah, Percut Sei Tuan District. This study uses the ADDIE development model which consists of five stages, namely analysis (Analyze), design (Design), Development (Development), Implementation (Implementation), Evaluation (Evaluation) because in this model the stages are used systematically. The data collection methods used in this study were observation, interviews and questionnaires, while the data collection techniques used were questionnaires. The data analysis technique used is a quantitative descriptive analysis technique. The subjects in this study were content experts, instructional design experts, learning media experts, as well as 25 students in class V-A as the experimental class and 25 students in class V-B as the control class at SDS Amir Hamzah. The population in this study were all students of class V-A SDS Amir Hamzah. The researcher chose a sample of class V-A SDS Amir Hamzah with a total of 25 students. The results of this study were the stages of analysis, design, development, implementation and evaluation. The results of research on the development of animated video-based learning media on Natural Resources (SDA) material in Class V-A meet very good/valid criteria with media expert test results reaching a validity level of 92%, material experts 81%, subject matter experts 87%, and linguists 83 %. The pretest score for measuring student learning outcomes reached 453 or 45.3% and the posttest score reached 815 or 81.5%. By obtaining the results of the N-gain test assessment resulting in an increase of 0.66, it can be concluded that the increase in the Higher Order Thinking Skill (HOTS) of students using animated video-based learning media belongs to the medium category for fifth grade students of SDS Amir Hamzah.